Flow diverter stent treatment for ruptured basilar trunk perforator aneurysms. (16th December 2014) - Peschillo, Simone; Caporlingua, Alessandro; Cannizzaro, Delia; Resta, Mariachiara; Burdi, Nicola; Valvassori, Luca; Pero, Guglielmo; Lanzino, Giuseppe
Abstract : Objective: Basilar trunk perforator (BTP) aneurysms are rare. Treatment options traditionally considered for these uncommon lesions have included direct surgery, endovascular therapy, or conservative management. Flow diverters represent a newer therapeutic option for BTP aneurysms but pitfalls and complications are unknown. We describe three patients with BTP aneurysms treated with flow diverter stents. Methods: All three patients had ruptured BTP aneurysms and, after loading doses of dual antiplatelet agents, underwent treatment with a flow diverter alone (two patients) or in combination with an intracranial stent (one patient). Results: Complications directly (two thromboembolic events) or indirectly (one hemorrhage at the external ventricular drain site, probably facilitated by the dual antiplatelet therapy) occurred in all three patients and resulted in permanent morbidity in one case. Imaging follow-up confirmed obliteration in all three patients, and no episodes of rebleeding from the aneurysms were observed at follow-up. Conclusions: Flow diverters are effective in obliterating BTP aneurysms. However, given the challenges and complications encountered, especially in patients with ruptured lesions, their use must be carefully weighed against other available therapeutic modalities, including observation.